Tawheed-Based Pedagogy: Empowering Islamic Education Through Community Engagement And Pesantren Tradition - Hosaini, Hosaini; Hamzah, Hamzah; Efendi, Moch. Yusuf; Simbolon, Nanci Yosepin; Sutiapermana, Aden (Journal Of Human And Education (JAHE), 2024)
Indonesia as a country with a Muslim majority population, has great potential to implement a tawhid-based educational approach in its education system. This approach, which emphasizes the oneness of Allah and the values ​​of tawhid in all aspects of life, can help overcome the complex challenges in education faced by the younger generation. Islamic boarding schools and Islamic educational institutions, such as the Sayyid Muhammad Alwi Al-Maliki Islamic Boarding School in Bondowoso, have become centers for character and moral development through the integration of tawhid in their curriculum. This holistic approach not only produces graduates who excel academically but also have high moral integrity, in accordance with Islamic religious values. Keywords: Tawhid-Based Pedagogy, Islamic Education, Community Engagement and Pesantren Traditions.